1996
DOI: 10.1046/j.1365-2141.1996.d01-1682.x
|View full text |Cite
|
Sign up to set email alerts
|

Myelodysplastic syndrome with karyotype abnormality is associated with elevated F‐cell production

Abstract: A sensitive F-cell assay has been used to examine the production of fetal haemoglobin (Hb F) in a group of 77 adult patients with myelodysplastic syndrome (MDS), and a control group composed of 100 normal blood donors. Although the mean F-cell percentage in the MDS group (6.0%) is not statistically different from that in the normal blood donors (3.1%), a higher proportion of myelodysplastic patients have elevated F-cell values and the magnitude of the increases is greater than that observed in blood donors. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 15 publications
(23 reference statements)
0
12
1
Order By: Relevance
“…The sample size of the present study was not high enough to allow for statistical comparisons of patients with different FAB subtypes. The association of increased hemoglobin F with karyotype abnormalities, as described by Craig et al [7], was not observed in our patients.…”
Section: Discussionmentioning
confidence: 47%
“…The sample size of the present study was not high enough to allow for statistical comparisons of patients with different FAB subtypes. The association of increased hemoglobin F with karyotype abnormalities, as described by Craig et al [7], was not observed in our patients.…”
Section: Discussionmentioning
confidence: 47%
“…14 Reactivation of HbF production in patients with MDS is a common phenomenon and an elevated F cell count has been reported to be a possible prognostic factor for MDS. 7,17,21 The present study is the first documentation that F blasts are found frequently in most patients with MDS. We investigated the F blast levels in MDS patients and non-MDS patients with stress erythropoiesis.…”
Section: Discussionmentioning
confidence: 92%
“…Similar data on HbF expression in erythrocytes were reported previously by other investigators, who found elevated HbF concentrations in up to 50% of MDS patients tested. 9,19,20 Craig et al 21 found that the mean F cell percentage in MDS patients was not statistically different from that in normal blood donors. In contrast, in the present study, HbF-containing erythrocytes in the bone marrow were seven times as abundant in patients with MDS as in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in F-cell or HbF levels parallels an improved clinical course in both sickle cell disease and thalassemia (Breymann et al, 1999;Nagel et al, 1993); however, since the therapies that induce increased F cells and HbF all have toxic side effects, it follows that therapeutic monitoring by F-cell enumeration should facilitate more optimal dosing for these patients. Additionally, studies have indicated that F-cell or HbF levels may be of prognostic value for evaluation of patients with myelodysplasia or thalassemia (Craig, Sampietro, Oscier, Contreras, & Thein, 1996;Liu, Seong, & Lin, 1997;Luna-Fineman et al, 1999;Reinhardt et al, 1998). Additionally, studies have indicated that F-cell or HbF levels may be of prognostic value for evaluation of patients with myelodysplasia or thalassemia (Craig, Sampietro, Oscier, Contreras, & Thein, 1996;Liu, Seong, & Lin, 1997;Luna-Fineman et al, 1999;Reinhardt et al, 1998).…”
Section: Of 17mentioning
confidence: 99%